Description of the Effectiveness of Using Online Media for Selling Pulsa: Deskripsi Keefektifan Penggunaan Media Online untuk Penjualan Pulsa - Frezy Paputungan (Jurnal Ilmu Manajemen dan Bisnis, 2022)
Online Media is a means to communicate online through websites and applications that can only be accessed via the internet. Contains text, sound, photos and videos. The definition of online media in general includes all types of websites and applications, including news sites, corporate sites, institutional/agency sites, blogs, community forums, social media sales sites (e-commerce/online stores) and chat applications. Events that occur in the field can be uploaded directly in minutes or seconds. Thus accelerating the distribution of information to the media, with global reach via the internet network, and at the same time. Updating information can be done easily and quickly, either in the form of improving content, data and grammar, or in the form of the latest development of an issue or event. When there is an update of information related to old information, changes can be made. This updating process can be done in real time. Online sales or e-commerce is an application and business process that connects shops and consumers through electronic transactions and can help the shop in marketing the maximum product. Lately, credit has become a basic need for both calling and using the internet. Selling credit using online media is needed by most people in Gorontalo City.